Randomized Controlled Trial of a Multilevel Intervention to Address Social Determinants of Refugee Mental Health. Issue 3 (17th February 2020) - Goodkind, Jessica R.; Bybee, Deborah; Hess, Julia Meredith; Amer, Suha; Ndayisenga, Martin; Greene, R. Neil; Choe, Ryeora; Isakson, Brian; Baca, Brandon; Pannah, Mahbooba
Highlights: Multilevel strengths‐based intervention decreases refugee distress and improves protective factors. Holistic focus on psychological, material, social, educational, and cultural needs is effective. High recruitment/retention rates support importance of non‐stigmatizing universal interventions. Refugee Well‐being Project (RWP) intervention reaches refugees unlikely to access formal mental health services. RWP circumvents typical barriers to services (stigma, trust, linguistic/cultural appropriateness). Abstract: Understanding processes that support the well‐being of the unprecedented numbers of forcibly displaced people throughout the world is essential. Growing evidence documents post‐migration stressors related to marginalization as key social determinants of refugee mental health. The goal of this RCT was to rigorously test a social justice approach to reducing high rates of distress among refugees in the United States. The 6‐month multilevel, strengths‐based Refugee Well‐being Project (RWP) intervention brought together university students enrolled in a 2‐semester course and recently resettled refugees to engage in mutual learning and collaborative efforts to mobilize community resources and improve community and systems responsiveness to refugees. Data collected from 290 Afghan, Great Lakes African, Iraqi, and Syrian refugees at four time points over 12 months were used to test the effectiveness of RWP to reduce distress (depression and anxiety symptoms) and increase protective factors (English proficiency, social support, connection to home and American cultures). Intention‐to‐treat analyses using multilevel modeling revealed significant intervention effects for all hypothesized outcomes. Results provide evidence to support social justice approaches to improving refugee mental health. Findings have implications for refugees worldwide, and for other immigrant and marginalized populations who experience inequities in resources and disproportionate exposure to trauma/stress.